Imaging artifacts of Onyx and PHIL on conventional CT, cone-beam CT and MRI in an animal model - Vollherbst, Dominik; Otto, Ruth; Do, Thuy; Kauczor, Hans-Ulrich; Bendszus, Martin; Sommer, Christof-Matthias; Möhlenbruch, Markus Alfred (Interventional neuroradiology, 2018)
Background and purposeA frequently reported drawback of ethylene vinyl alcohol copolymer-based liquid embolic agents is the production of artifacts in diagnostic imaging. New embolic agents, such as Precipitating hydrophobic injectable liquid (PHIL; MicroVention, Tustin, CA, USA), are supposed to induce significantly fewer artifacts. The purpose of this study is to assess the degree of artifacts induced by the liquid embolic agents Onyx (Medtronic Neurovascular, Irvine, CA, USA) and PHIL in conventional computed tomography (CT), cone-beam CT and magnetic resonance imaging (MRI) in an experimental in vivo model.Materials and methodsIn 10 pigs the rete mirabile was embolized with Onyx (n?=?5) or PHIL (n?=?5). After embolization, conventional CT, cone-beam CT and MRI were performed. The degree of artifacts was graded qualitatively (five-point scale; for CT and MRI) and quantitatively (HUs of well-defined regions of interest (ROIs); for CT only).ResultsArtifacts were significantly more severe for Onyx both in the qualitative (e.g. conventional CT: 2 versus 5 (medians); p?=?0.008) and in the quantitative image analysis (e.g. cone-beam CT: standard deviation of a ROI near to the embolic agent cast, 94 HU versus 38 HU (medians); p?=?0.008). Neither Onyx nor PHIL produced any apparent artifacts in MRI.ConclusionPHIL produces fewer artifacts than Onyx in conventional CT and cone-beam CT in an experimental in vivo model.
Gesehen am 29.03.2019